(untitled) (Contemporary Journal of Social Science Review, 2026)
Anxiety and stress are common issues among undergraduate nursing students because nursing education is both academic and clinical. Students in private hospital clinical settings may face additional pressure from the clinical workload, patient-care responsibilities, academic demands, financial concerns and professional expectations. The objective of the study was to assess the anxiety and stress level of the undergraduate nursing students in private hospitals. The design of this study was descriptive research design. A non-probability convenience sampling method was used to select 30 undergraduate nursing students that were available and willing to participate during the data collection period. Data were collected using a structured questionnaire consisting of demographic data and anxiety and stress items. The reliability of the instrument was acceptable with Cronbach’s alpha = 0.732. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used to analyze the data. Results indicated that the undergraduate nursing students experienced anxiety prior to starting clinical shifts and stress related to clinical workload, problems in balancing academic studies with hospital duties, frequent tests and assignments, financial pressure, availability of counselling support, and mental health issues. The highest mean scores for the anxiety and stress related items were scored for feeling anxious before starting a clinical shift and availability of counselling or support systems . Mean of 1.27 for other items including clinical workload, balancing studies with hospital duties, use of exercise, unmanageable tests and assignments. Mean of 1.10 for financial stress and worry about mental health Proper clinical orientation, supportive supervision, counselling services, balanced academic and clinical workload and stress management programmes were suggested to reduce anxiety and stress among undergraduate nursing students in nursing colleges and private hospitals.